2006
DOI: 10.1108/13590790610641260
|View full text |Cite
|
Sign up to set email alerts
|

Problems controlling fraud and abuse in the home health care field

Abstract: PurposeThe purpose of the current study is to assess the efforts to control fraud in the home health care industry in the USA by examining the problems that criminal justice officials confronted in their attempts to control home health care fraud and abuse.Design/methodology/approachAttention is given to the history of the home health care industry in the USA, the types of fraud found in the health care field in general, and the officials who are given the duty of controlling health care fraud.FindingsThe resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In particular, mental health professionals, namely psychologists and psychiatrists, comprise a disproportionate amount of Medicaid and Medicare fraud perpetrators (Geis et al 1985a;Pontell et al 1985;Payne 1995). A study by Geis and colleagues found that psychiatrists made up over 18% of those sanctioned for a Medicaid and=or Medicare violation (Geis et al 1985a;Pontell et al 1985).…”
Section: Literature Reviewmentioning
confidence: 95%
See 3 more Smart Citations
“…In particular, mental health professionals, namely psychologists and psychiatrists, comprise a disproportionate amount of Medicaid and Medicare fraud perpetrators (Geis et al 1985a;Pontell et al 1985;Payne 1995). A study by Geis and colleagues found that psychiatrists made up over 18% of those sanctioned for a Medicaid and=or Medicare violation (Geis et al 1985a;Pontell et al 1985).…”
Section: Literature Reviewmentioning
confidence: 95%
“…Kickbacks involve the solicitation or compensation for products or services for which Medicaid reimburses the provider (Hyman 2001). Kickbacks can also involve instances where a provider receives some sort of payment for referring a patient to another provider (Payne 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They connect the presence of motivated offenders to caregiving strain, low job satisfaction, perceived unfairness of working conditions and nurses' low self-control. Payne and Fletcher (2005) and Payne andGainey (2006, 2007) also have taken a routine activities perspective on abuse in institutional care. Payne (2006) and Setterlund et al (2007) have applied RAT concepts to financial elder abuse, Dietz and Wright (2005) to the topic of victimization of older homeless people.…”
Section: Routine Activity Theorymentioning
confidence: 99%